Analysis Of Disaster Training Needs in Malang Regency - Vanya Eka Pratiwi; Joko Santoso; Rahman Hakim (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Malang Regency has a high level of disaster risk due to its diverse geographical conditions, while the community’s level of preparedness remains in the moderate category. Through the Regional Disaster Management Agency (BPBD), the local government has implemented various disaster training programs tailored to the types of threats present. However, the implementation of these training programs has not yet fully reached all areas in an equitable and sustainable manner. This study aims to analyze the needs for disaster training in Malang Regency. The method used is a qualitative descriptive approach through the analysis of secondary data related to disaster events, regional risk levels, and regional resilience indices, as well as the collection of primary data through semi-structured interviews with BPBD officials regarding the implementation of training programs and outreach activities. The results of the study indicate that there is a need to strengthen the capacity of local instructors, ensure equitable access to training—particularly in high-risk areas—implement simulation-based training methods on a sustainable basis, and provide disaster education and training facilities as integrated support for learning, simulation, and community capacity building. These efforts are expected to enhance community preparedness and strengthen regional resilience in facing future disasters.